2023
DOI: 10.1371/journal.pone.0270386
|View full text |Cite
|
Sign up to set email alerts
|

How long can tardigrades survive in the anhydrobiotic state? A search for tardigrade anhydrobiosis patterns

Abstract: Anhydrobiosis is a desiccation tolerance that denotes the ability to survive almost complete dehydration without sustaining damage. The knowledge on the survival capacity of various tardigrade species in anhydrobiosis is still very limited. Our research compares anhydrobiotic capacities of four tardigrade species from different genera, i.e. Echiniscus testudo, Paramacrobiotus experimentalis, Pseudohexapodibius degenerans and Macrobiotus pseudohufelandi, whose feeding behavior and occupied habitats are differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 71 publications
1
12
0
Order By: Relevance
“…Anhydrobiosis in tardigrades is a complex phenomenon. It includes entering, permanent, and leaving steps, which correspond to dehydration (tun formation), tun state (desiccated state), and rehydration, respectively [ 31 ]. These steps are well known at the level of the organism’s morphology [ 32 ], but a full understanding of their mechanisms requires the consideration of additional factors.…”
Section: Introductionmentioning
confidence: 99%
“…Anhydrobiosis in tardigrades is a complex phenomenon. It includes entering, permanent, and leaving steps, which correspond to dehydration (tun formation), tun state (desiccated state), and rehydration, respectively [ 31 ]. These steps are well known at the level of the organism’s morphology [ 32 ], but a full understanding of their mechanisms requires the consideration of additional factors.…”
Section: Introductionmentioning
confidence: 99%
“…(2009), who tested Δ recovery (difference between motility at 1 and 24 h after rehydration) in a population then identified as ‘ P. richtersi ’ (now known to represent as P. spatialis Guidetti et al., 2019) at different desiccation conditions. Two other studies (Roszkowska et al., 2023; Roszkowska, Gołdyn, et al., 2021) tested the recovery time (as time to movement after rehydration) against the anhydrobiosis duration. We found that the two components— p and Q —despite being generally correlated, can still show a non‐negligible independence (Figure 3) and should therefore be considered jointly when analysing anhydrobiotic performance.…”
Section: Discussionmentioning
confidence: 99%
“…Despite decades of research on anhydrobiosis, most of the research effort has been devoted to the understanding of the physiological and molecular mechanisms that allow animals to survive almost complete desiccation (see any of the many reviews published on the topic, for example: Arakawa, 2022; Hibshman et al., 2020; Rebecchi et al., 2020; Sogame & Kikawada, 2017). In contrast, the interplay between anhydrobiosis and evolutionary processes or how evolutionary and ecological pressures lead to this astonishing adaptation are still poorly studied (Kaczmarek et al., 2019; McGill et al., 2015; Ricci & Caprioli, 2005; Roszkowska et al., 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All terrestrial (i.e., living in moss, lichen, and soil) and aquatic (marine and freshwater) dwelling tardigrades, require a layer of liquid water to be active. Despite this, if in their substrate the water becomes unavailable, for example, by freezing or evaporation, many tardigrade species can enter a suspended cryptobiotic life state or form cysts (Bertolani et al, 2019; Guidetti et al, 2011; Janelt & Poprawa, 2020; Møbjerg et al, 2011; Rebecchi et al, 2007, 2020; Roszkowska et al, 2020, 2023; Møbjerg & Nives, 2021). Tardigrades can withstand many harsh environmental stressors (such as radiations, pollutants, and others), both in their hydrated state, as well as in their cryptobiotic state (e.g., Altiero et al, 2011; Giovannini et al, 2018; Horikawa et al, 2006; Hygum et al, 2017; for a review see Møbjerg & Neves, 2021).…”
Section: Introductionmentioning
confidence: 99%